Can someone help me solve this algebraically? I’ll give brainliest!!
![Can someone help me solve this algebraically Ill give brainliest class=](https://us-static.z-dn.net/files/dd4/bdedec35d5aa94d0c4f62178d00d0bf6.png)
Answer:
Your solution was correct.
Step-by-step explanation:
y = 3x + 5
y = 2x - 1
(-6,-13) ?
Rearrange equations and eliminate the y variable to solve for x variable:
y = 3x + 5 ---> y - 5 = 3x
y = 2x - 1 ---> y + 1 = 2x
Subtract the bottom equation from the top equation:
-5 = 3x
1 = 2x
-6 = x
Substitute x = -6 into y = 2x - 1
y = 2x - 1
y = 2(-6) - 1
y = -12 - 1
y = -13